Incidencia de la pobreza multidimensional en la pobreza monetaria en el departamento de Loreto durante el año 2023 - Cuellar Valles, Emily Zamanta (2025)
This research analyzes the incidence of multidimensional poverty on monetary poverty in the department of Loreto during the year 2023. Multidimensional poverty is addressed by considering factors such as educational level, informal employment, and access to basic and health services, in order to evaluate its impact on the monetary poverty condition of the PEAO in Loreto. The study is quantitative, explanatory level, and non-experimental design with cross sectional data, with a study population made up of 553,820. The study determined that, for each increase in educational level, the probability of being in a situation of monetary poverty decreases by approximately 9.19 percentage points. Likewise, having an informal job and not having access to all basic services reduces the probability of being in a situation of monetary poverty by 10.94 and 28.94 percentage points, respectively.